Taxonomic and nomenclatural notes on Brazilian Dichorisandra (Commelinaceae) - Aona, Lidyanne Yuriko Saleme; Bittrich, Volker; Amaral, Maria Do Carmo E. (Phytotaxa, 2018)
Based on a revision of Dichorisandra (Commelinaceae), this work proposes new synonyms and designates types for 14 species that occur in Brazil. Comments on the taxonomy, nomenclature, and the distribution and habitats occupied by each of these species are provided.